Emerging Technologies: It’s Not What YOU Say – It’s What THEY Do - Cook, Vickie S; Gregory, Rhonda L. (Online Learning, 2018)
This paper is provided for OLC 2018 Special Edition from a 2018 InnovatePresentation in Nashville Tennessee. We will explore various emerging technologies at the writing of this article. It is important to note that, the authors believe that learning is not a complete circle when evaluated by what educators do, the technologies we use, nor how we communicate our knowledge to our students. Learning is only successful when we fully assess the impact of our preparations and presentations on student outcomes. Students need the opportunity to actively participate in the doingof learning. Modeling the literacies needed to skillfully enable us to meet the needs of our future world through strong use of technologies in a huetagogical setting enables learning success.